Biochemical characterization of Arabidopsis clade F polygalacturonase shows a substrate preference toward oligogalacturonic acids - Ohashi T. (2023)
Polygalacturonases (PGs) hydrolyze α-1,4-linked D-galacturonic acid (GalUA) in polygalacturonic acid. Previously, PG activity in pea seedlings was found in the Golgi apparatus, where pectin biosynthesis occurs. However, the corresponding genes encoding Golgi-localized PG proteins have never been identified in the higher plants. In this study, we cloned the 5 Arabidopsis genes encoding putative membrane-bound PGs from clade F PGs (AtPGFs) as the first step for the discovery of the Golgi-localized PGs. Five AtPGF proteins (AtPGF3, AtPGF6, AtPGF10, AtPGF14 and AtPGF16) were heterologously produced in Schizosaccharomyces pombe. Among these, only the AtPGF10 protein showed in vitro exo-type PG activity toward fluorogenic pyridylaminated-oligogalacturonic acids (PA-OGAs) as a substrate. The optimum PG activity was observed at pH 5.5 and 60°C. The recombinant AtPGF10 protein showed the maximum PG activities toward PA-OGA with 10 degrees of polymerization. The apparent Km values for the PA-OGAs with 7, 11 and 14 degrees of polymerization were 8.0, 22, and 5.9 μM, respectively. This is the first report of the identification and enzymatic characterization of AtPGF10 as PG carrying putative membrane-bound domain.